Determinants that Influence the Decision of Nazhir in Investing in the Sharia Capital Market - Abelian, Ridlo; Khalil, Jafril (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Islamic capital market is one of the Islamic financial instruments, the development of the Islamic capital market is quite good in Indonesia, but investors from nazir waqf have not been very active in investing in the Islamic capital market. The purpose of this study was to examine the effect of the variables knowledge, motivation, and minimum capital on investment on the Nazhir Decision variable in developing waqf assets in the Islamic capital market. The research object is Islamic capital market while the population is Islamic capital market Nazir, the sampling technique uses random sampling technique of 140 respondents. Collective data used a questionnaire using a Linkert scale with a scale of 1 to 5. The data analysis technique used a structural equation model (SEM) with SmartPLS software. The results of the study prove that the independent variable Islamic knowledge has a significant effect on the decision to invest in the Islamic capital market. The minimum capital deposit has a significant and positive influence on Nazir's decision to invest in the Islamic and variable capital markets. The motivational variable has no significant effect on Nazir's decision to invest in the Islamic capital market